IDENTIFICATION OF MULTICULTURALISM VALUES IN INDONESIAN HISTORY TEXTBOOKS IN CURRICULUM OF 2013 - Lionar, Uun (Universitas Pendidikan Indonesia, 2017)
Indonesia is a multicultural country in which there are various ethnic, tribal, religious, and cultural elements spread out on various islands. In order to maintain the diversity from the nation disintegration threat, it is needed to have a conceptualized strategy through various aspects of life. With respect to the field of education, the concept of multicultural is internalized through the learning materials contained in the textbook. The textbook of history subject is basically set up by the government of the Republic of Indonesia in order to convey a message of values which is relevant to Pancasila as the nation's ideology. In regard to this nation’s ideology, multiculturalism in fact is considered as one of its values. Through this study, the writer will then analyze the textbook of Indonesian History subject of class X, in the first semester based on the curriculum of 2013, by identifying the values of multiculturalism contained within this aforementioned textbook. This book consists of two chapters. In particular, the first chapter discusses the materials on the spread of early civilizations in the Indonesian archipelago, and the second chapter covers the trades, rulers, and poets in the classical period (Hinduism-Buddhism). This present study employed a qualitative approach with a syntagmatic discourse analysis method, specifically using a constructivism paradigm. In particular, this method attempted to find out various facts behind a script in which one of them also included ideological and political elements. With respect to the use of constructivism paradigm, it was also used to discover something in the form of feelings / desires of the script maker. Based on the carried-out analysis, the writer found several paragraphs that implicitly contained the values of multiculturalism. The value was conveyed through various instances in the historical events. Therefore, the writer concluded that in the textbook of Indonesian History subject of Class X in the first semester, the curriculum of 2013 contained the values of multiculturalism. Although it was not explicitly stated, the ideas of multiculturalism should be reaffirmed by the teacher during the learning processes.